Rapid Adaptation of Renewable Energy – A Review on Solar Energy, Types and Overview - S.P.Meena (Recent Research Reviews Journal, 2022)
Renewable energy is derived from the sources that can be renewed naturally. The majority of renewable energy sources obtained from sunlight, wind, water currents, and geothermal heat, are sustainable. Solar energy, wind energy, hydropower, geothermal energy, and other forms of renewable energy utilize a variety of methods to generate renewable resources. The sun has the potential to meet the entire world's energy requirements. Solar energy has the capacity to be efficiently and economically converted into electricity by remaining as a renewable energy source. This article will explain about the solar energy, its overview, evolution, different forms, advantages, and disadvantages.
Keywords: Renewable energy; solar energy; photovoltaic energy; concentrated solar power; and passive solar water heater